Further structural insights into the binding of complement factor H by complement regulator-acquiring surface protein 1 (CspA) of Borrelia burgdorferi - Caesar, Joseph J. E.; Wallich, Reinhard; Kraiczy, Peter; Zipfel, Peter F.; Lea, Susan M. (Acta crystallographica. Section F, Structural biology communications, 2013)
B. burgdorferi binds complement factor H using a dimeric surface protein, CspA (BbCRASP-1). Presented here is a new structure of CspA that suggests that there is a degree of flexibility between subunits which may have implications for complement regulator binding., - Borrelia burgdorferi has evolved many mechanisms of evading the different immune systems across its range of reservoir hosts, including the capture and presentation of host complement regulators factor H and factor H-like protein-1 (FHL-1). Acquisition is mediated by a family of complement regulator-acquiring surface proteins (CRASPs), of which the atomic structure of CspA (BbCRASP-1) is known and shows the formation of a homodimeric species which is required for binding. Mutagenesis studies have mapped a putative factor H binding site to a cleft between the two subunits. Presented here is a new atomic structure of CspA which shows a degree of flexibility between the subunits which may be critical for factor H scavenging by increasing access to the binding interface and allows the possibility that the assembly can clamp around the bound complement regulators.
Gesehen am 28.01.2021